Pengelolalan Pembiayaan Pendidikan di SMK Muhammadiyah 6 Gemolong Sragen - Leonarti, Miss Agustina; , Dr. Suyatmini, MSi; , Dr. Sabar Narimo, MM, MPd (2015)
This study aimed to describe about (1) the planning Financing Education in SMK Muhammadiyah 6 Gemolong Sragen; (2) funding of education at SMK Muhammadiyah 6 Gemolong Sragen; (3). Funding Accountability in SMK Muhammadiyah 6 Gemolong Sragen; (4) Obstacles encountered in the management of financing at SMK Muhammadiyah 6 Gemolong Sragen. The method in this study using qualitative research with an ethnographic approach. The method used in data collection is interview, observation and documentation. This study was conducted in SMK Muhammadiyah 6 Gemolong Sragen from April until the month of May 2015. To test the validity of the data using triangulation of data and methods to the criteria of degree of confidence (Kredibility), keteralihan (transferability), dependability (dependability) and certainty (confirmability) .Teknik data analysis include: data reduction, data presentation and conclusion / verification. Analysis of the data in penelitiankualitatif is the process of simplification of data into a form that is easily read and interpreted. The conclusion of this research is the process of managing the financing of education at SMK Muhammadiyah 6 Gemolong Sragen through the process of budget planning, implementation and monitoring and accountability. Management of education funding in SMK Muhammadiyah 6 Gemolong Sragen has been implemented in a transparent, effective and efficient. At the time of budget preparation involves teams representing the parts that exist in schools. Management of education funding in SMK Muhammadiyah 6 Gemolong Sragen supported by the school authority to regulate the management of financing independently and do not depend on the foundation, but it also forces managers reliable ability to manage financing so that the smooth pengelolaan.Kendala encountered in the management of the financing is delay students in paying tuition and delay decline in BOS.